Religious tourism and heritage in Brazil - Oliveira, Christian Dennys Monteiro de (SpringerBriefs in Latin American studies,, 2016)
The book reflects on the current dimensions of tourism and patrimony in Brazil. It presents cultural realities as resources for the resolution of tensions between different communities and the establishment of their identities. The book also presents memories and forgotten traditions that are important in the representation of places and cultures. It questions religious systems and their dynamic interface with the occupation of cultural spaces and the interpretation of touristic practices in Brazil. The topics discussed include pilgrimages, sanctuaries, symbolic vectors, and religious festivals.- Resumé vydavatel